Bagaimana Hubungan antara Tingkat Pengetahuan dan Jumlah Sisa Akar Gigi Pada Pasien Usia 20-60 Tahun di Klinik Terapis Gigi Mappaoddang Makassar? - Pariati; Muhammad Adam, Andi; Iyabu, Novia; Sundu, Suciyati (Media Kesehatan Gigi : Politeknik Kesehatan Makassar, 2023)
Knowledge about dental and oral health is something that a person knows about maintaining dental health. A common problem faced regarding dental and oral health problems is the presence of remaining roots, which is a condition where the crown of the tooth is lost due to caries which has destroyed the tooth enamel so that only the root remains. This study aims to determine whether there is an influence between knowledge of remaining tooth roots in patients aged 20-60 years at the Mappaodang Dental Therapist Clinic, Makassar. This research is a quantitative research by processing validated questionnaire data and then carrying out a statistical test of the linearity of the relationship between the respondent's knowledge and the remaining tooth roots. The results of this research are that there is a relationship between knowledge on the remaining tooth roots as shown by the statistical test data. The calculated F value is 33.152 with a significance level of 0.000 < 0.005, which means there is a relationship between the independent variable (knowledge) and the dependent variable (Y).